2012
DOI: 10.1002/chem.201101835
|View full text |Cite
|
Sign up to set email alerts
|

Facile Carbon–Fluorine Bond Activation and Subsequent Functionalisation of 1,1‐Difluoroethylene and Tetrafluoroethylene Promoted by Adjacent Metal Centres

Abstract: The bridging fluoroolefin ligands in the complexes [Ir(2)(CH(3))(CO)(2)(μ-olefin)(dppm)(2)][OTf] (olefin = tetrafluoroethylene, 1,1-difluoroethylene; dppm = μ-Ph(2)PCH(2)PPh(2); OTf(-) = CF(3)SO(3)(-)) are susceptible to facile fluoride ion abstraction. Both fluoroolefin complexes react with trimethylsilyltriflate (Me(3)SiOTf) to give the corresponding fluorovinyl products by abstraction of a single fluoride ion. Although the trifluorovinyl ligand is bound to one metal, the monofluorovinyl group is bridging, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 103 publications
1
12
0
Order By: Relevance
“…Note that fluorinated vinyl entities can be rather stable at transition metal centres. 43,[131][132][133][134][135][136][137][138][139][140] However, a reaction of 8 with dihydrogen resulted in the formation of [Pt{N(SO 2 Ph) 2 }(H){κ 2 -(P,N)-iPr 2 PC 2 H 4 NMe 2 }] (12) and the fluorinated organic product (Z)-(1-fluoroethene-1,2-diyl)dibenzene.…”
Section: Discussionmentioning
confidence: 99%
“…Note that fluorinated vinyl entities can be rather stable at transition metal centres. 43,[131][132][133][134][135][136][137][138][139][140] However, a reaction of 8 with dihydrogen resulted in the formation of [Pt{N(SO 2 Ph) 2 }(H){κ 2 -(P,N)-iPr 2 PC 2 H 4 NMe 2 }] (12) and the fluorinated organic product (Z)-(1-fluoroethene-1,2-diyl)dibenzene.…”
Section: Discussionmentioning
confidence: 99%
“…The reaction employing (dppp)NiCl 2 in place of (dppp) PdCl 2 as a catalyst in the presence of an excess amount of ( p-tol)MgBr affords the bis-substituted product as a major product. Our group has achieved the first catalytic transformation of tetrafluoroethylene (TFE; CF 2 ¼CF 2 ) [60], whereas C-F bond activation of TFE was accomplished in a few stoichiometric reactions [61][62][63][64][65]. In the presence of lithium iodide and a catalytic amount of Pd 2 (dba) 3 , the Negishi-type cross-coupling reaction of TFE with a variety of diarylzinc reagents proceeds in THF at 40 C, yielding the corresponding α,β,β-trifluorostyrene derivatives (Scheme 20).…”
Section: Group 9 Metal Catalystmentioning
confidence: 99%
“…First, a comparison of [Ir 2 (CO) 3 (μ-H)(depm) 2 ] + (1) and its dppm analogue has shown that, while the latter is unreactive to all fluoroolefins studied in this report, the depm compound (1) reacts readily with all of them. Second, although we had observed water-promoted C−F activation in some of the previous dppm chemistry, 68,69 this involvement was not nearly as extensive as it has proven to be in the current depm system, as will be discussed. Furthermore, in much of the chemistry reported herein, the smaller size of depm (and possibly its greater basicity) has allowed the incorporation of two fluoroolefin-derived fragments, whereas with dppm, only a single fluorocarbyl unit was incorporated.…”
Section: Discussionmentioning
confidence: 79%
“…The acetylide-bridged product (4) is highly reminiscent of the propynyl-bridged analogue, observed in the activation of 1,1-difluoroethylene by a dppm-bridged methyl complex. 69 Complex 4 displays a broad singlet in the 31 P{ 1 H} NMR spectrum, which changes little upon cooling to −80 °C, while the quintet at δ 181.6 ( 2 J CP = 5.6 Hz) in the 13 C{ 1 H} NMR spectrum of a 13 CO-enriched sample broadens slightly upon cooling. The static structure proposed should display two 31 P resonances, owing to the chemical inequivalence of both metals, and should also display three carbonyl resonances.…”
Section: B Resultsmentioning
confidence: 99%
See 1 more Smart Citation